STUDI PERBANDINGAN KETERSEDIAAN SARANA DAN PRASARANA PENDIDIKAN DI SEKOLAH DI KAWASAN PERKOTAAN DAN PERDESAAN - Sudiro, Fadhillah Sabrina; Nasir, Nasir; Lilianti, Lilianti; Mujiati, Mujiati (Jurnal Isema : Islamic Educational Management, 2024)
A successful and high-quality learning environment requires adequate educational facilities. But the disparities between urban and rural areas frequently impact the standard of facilities in both places. The comparative descriptive study design is used to gather data from direct observations and interviews with the school's head and representatives from the other two relevant institutions. The information gathered covers details about the accessibility of facilities, the state of school buildings, and other learning support facilities. The study's findings indicated that facilities for sports and extracurricular activities are more readily available in urban than rural locations. The city has a state-of-the-art educational facility with practical classrooms, sufficient libraries, and labs. Urban areas also have more reliable and open internet connections. On the other hand, rural schools have physical limitations due to the size of the classrooms and the lack of adequate learning support resources. The availability of educational amenities between urban and rural schools differs significantly, in conclusion. For all kids, regardless of where they are in the world, the infrastructure and technological accessibility issues in rural schools need to be given more consideration. To achieve educational equity throughout the Indonesian area, governments and stakeholders must make improvements and use funds wisely.